Antileishmanial Activity and Immunomodulatory Effects of Tricin Isolated from Leaves of Casearia arborea (Salicaceae) - Santos, Augusto L.; Yamamoto, Eduardo S.; Passero, Luiz Felipe D. [UNESP]; Laurenti, Márcia D.; Martins, Ligia F.; Lima, Marta L.; Uemi, Miriam; Soares, Marisi G.; Lago, João Henrique G.; Tempone, Andre G.; Sartorelli, Patricia (Wiley, 2017)
Bioactivity-guided fractionation of antileishmanial active extract from leaves of Casearia arborea led to isolation of three metabolites: tricin (1), 1′,6′-di-O-β-d-vanilloyl glucopyranoside (2) and vanillic acid (3). Compound 1 demonstrated the highest activity against the intracellular amastigotes of Leishmania infantum, with an IC50 value of 56 μm. Tricin (1) demonstrated selectivity in mammalian cells (SI > 7) and elicited immunomodulatory effect on host cells. The present work suggests that tricin modulated the respiratory burst of macrophages to a leishmanicidal state, contributing to the parasite elimination. Therefore, the natural compound tricin could be further explored in drug design studies for leishmaniasis treatment.
Keywords: Casearia arborea; Divanilloyl glucopyranoside; Immunomodulation; Leishmania; Salicaceae; Tricin; Vanillic acid